Distribution of crop wild relatives of conservation priority in the UK landscape. (November 2015) - Jarvis, Susan; Fielder, Hannah; Hopkins, John; Maxted, Nigel; Smart, Simon
Abstract: Many crop species suffer from a lack of genetic diversity which reduces the ability of cultivars to withstand new pests or environmental stresses. The wild relatives of crop plants are an important source of genetic variation and can be used to introduce new traits into existing crops. Identification and conservation of crop wild relatives (CWR) is, therefore, an important step to safeguard future food security. Recent efforts have identified geographical hotspots of CWR diversity in several countries but, as yet, there have been no surveys to identify the habitats and landscape features within these areas that might be most suitable for conservation efforts. Here, we use a UK-wide vegetation survey covering a range of both habitats and landscape features (e.g. fields, hedgerows, waterways and roadsides) to identify the habitats and features with the highest proportion of CWR identified as priority taxa for conservation. Priority CWR were most abundant in grassland habitats, although this was most striking in CWR related to forage and fodder crops. CWR related to food crops were most common in cropped and weedy areas, fertile grassland and lowland woodland. Within habitats, CWR occurrence was significantly associated with linear features including hedgerows, roadsides, field boundaries and field margins. Our findings indicate that CWR of conservation interest are often associated with disturbed habitats and landscape features that are not considered as priorities under site-based conservation measures. We suggest that efforts to maintain linear features in hotspots of CWR diversity would be most effective at conserving the UK's CWR resource. Highlights: We quantified the distribution of crop wild relatives (CWR) in the UK landscape. Grasslands were the habitat with the highest number of CWR of conservation priority. Priority CWR were also frequent in hedges, field margins and road verges. This highlights the importance of linear features in intensively managed landscapes. Guidelines for habitat-based CWR conservation are discussed.